Analysis of the Challenges to Program without Seeing: study case study in Programming Language 1 - Gonçalves, Raul Santos; Santana, Robson Santos; Anacreonte Neto, Francisco; Benevides, Saullo Cruz; dos Santos, Naiara Silva (Companion Proceedings of the Brazilian Symposium on Information Systems (SBSI); 2020: Companion Proceedings of the 16th Brazilian Symposium on Information SystemsDO - 10.5753/sbsi.2020.13118, 2020)
Screen readers make it possible for blind programmers to implement the code because they can hear what they are typing, but these programs have problems. This article describes the case study and analyzes the problems faced by blind programmers in the act of programming. Data were collected during the classes of the Programming Language 1 course. The DOSVOX screen reader and the C language compilers were used: Dev C ++, Falcon and CodeBlocks.